Genome-wide analysis and molecular dissection of the SPL gene family in Salvia miltiorrhiza - Zhang, Linsu; Wu, Bin; Zhao, Degang; Li, Caili; Shao, Fenjuan; Lu, Shanfa (Journal of integrative plant biology, 2014)
SQUAMOSA promoter binding protein‐likes (SPLs) are plant‐specific transcription factors playing vital regulatory roles in plant growth and development. There is no information about SPLs in Salvia miltiorrhiza (Danshen), a significant medicinal plant widely used in Traditional Chinese medicine (TCM) for >1,700 years and an emerging model plant for TCM studies. Through genome‐wide identification and subsequent molecular cloning, we identified a total 15 SmSPLs with divergent sequence features, gene structures, and motifs. Comparative analysis showed sequence conservation between SmSPLs and their Arabidopsis counterparts. A phylogenetic tree clusters SmSPLs into six groups. Many of the motifs identified commonly exist in a group/subgroup, implying their functional redundancy. Eight SmSPLs were predicted and experimentally validated to be targets of miR156/157. SmSPLs were differentially expressed in various tissues of S. milltiorrhiza. The expression of miR156/157‐targeted SmSPLs was increased with the maturation of S. miltiorrhiza, whereas the expression of miR156/157 was decreased, confirming the regulatory roles of miR156/157 in SmSPLs and suggesting the functions of SmSPLs in S. miltiorrhiza development. The expression of miR156/157 was negatively correlated with miR172 during the maturation of S. miltiorrhiza. The results indicate the significance and complexity of SmSPL‐, miR156‐, and miR172‐mediated regulation of developmental timing in S. miltiorrhiza.